Protective effect of naringenin on cadmium chloride-induced renal injury via alleviating oxidative stress, endoplasmic reticulum stress, and autophagy in chickens - Shi, Yaning; Gao, Zhixin; Xu, Bing; Mao, Junbing; Wang, Yue; Liu, Zongping; Wang, Jicang (Frontiers in Pharmacology, 2024)
Cadmium (Cd) is a highly hazardous toxic substance that can cause serious harm to animals. Previous studies have indicated that cadmium chloride (CdCl2) can damage organs, such as the liver, ovaries, and testicles. Naringenin (Nar) represents a flavonoid with various properties that promote the alleviation of Cd-induced damage. In this experiment, 60 chickens were divided into the control group, 150 mg/kg CdCl2 treatment group, 250 mg/kg Nar treatment group, and 150 mg/kg CdCl2 + 250 mg/kg Nar co-treatment group, which were treated for 8 weeks. Kidney tissues samples were collected to investigate kidney function, including oxidative stress (OS), endoplasmic reticulum (ER) stress, and autophagy activity. Experimental results showed the decreased weight of chickens and increased relative weight of their kidneys after CdCl2 treatment. The increase in NAG, BUN, Cr, and UA activities, as well as the increase in MDA and GSH contents, and the decrease activities of T-AOC, SOD, and CAT in the kidney, manifested renal injury by OS in the chickens. TUNEL staining revealed that CdCl2 induced apoptosis in renal cells. CdCl2 upregulates the mRNA and protein expression levels of GRP78, PERK, eIF2α, ATF4, ATF6, CHOP, and LC3, and inhibited the mRNA and protein expression levels of P62 proteins, which leads to ER stress and autophagy. The CdCl2 + Nar co-treatment group exhibited alleviated CdCl2-induced kidney injury, OS, ER stress, and autophagy. Research has demonstrated that Nar reduces CdCl2-induced kidney injury through alleviation of OS, ER stress, and autophagy.